2012
DOI: 10.1364/ol.37.000563
|View full text |Cite
|
Sign up to set email alerts
|

Sub-100 nm structuring of indium-tin-oxide thin films by sub-15 femtosecond pulsed near-infrared laser light

Abstract: In magnetron sputtered indium-tin-oxide thin films of varying oxygen content, nanostructures were formed using tightly focused high-repetition rate near-infrared sub-15 femtosecond pulsed laser light. At radiant exposure well beyond the ablation threshold, cuts of 280-350 nm in width were generated. Illumination close to the ablation threshold resulted in periodic cuts of typically 20 nm in width at periodicities between 50 nm and 180 nm, as well as single sub-20 nm cuts. Subthreshold exposure, in combination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…Samples termed ITO-2 were produced with 2 sccm oxygen flow (total flow 60 sccm, chamber pressure 0.003 mbar). The electrical and optical properties of ITO as n-type wide-band gap semiconductor (band gap 3.5 -4.1 eV [8,14,15]) strongly depend on the oxygen content [16]. A specific resistivity of ITO-2 of 3.9 x 10 -4 Ω cm was determined by the van-der-Pauw method in accordance with earlier experiments [16].…”
Section: Ito Film Deposition and Ma-n Photoresist Coatingsupporting
confidence: 59%
See 1 more Smart Citation
“…Samples termed ITO-2 were produced with 2 sccm oxygen flow (total flow 60 sccm, chamber pressure 0.003 mbar). The electrical and optical properties of ITO as n-type wide-band gap semiconductor (band gap 3.5 -4.1 eV [8,14,15]) strongly depend on the oxygen content [16]. A specific resistivity of ITO-2 of 3.9 x 10 -4 Ω cm was determined by the van-der-Pauw method in accordance with earlier experiments [16].…”
Section: Ito Film Deposition and Ma-n Photoresist Coatingsupporting
confidence: 59%
“…Due to the ITO-2 absorption edge wavelength of 420 nm multiphoton excitation is expected to dominate the ablation process [16]. Operating extremely close to the ablation threshold, tiny rifts perpendicular to the laser polarization appeared at fairly regular space intervals.…”
Section: Nanopatterning and Cutting Of Ito Thin Film Electrodes By Sumentioning
confidence: 99%
“…Ablative LIPSS aligned perpendicular to the laser beam polarization (⊥-LIPSS) and periods as small as ≈λ/15 have been observed in films irradiated with high repetition rate, fs laser pulses at 800 nm at extremely slow scanning speeds ( ≈10´s µm s −1 ). [21] At a much lower repetition rate, Wang et al [22] observed periodic arrangements of nanolines and nanodots with longer, multimodal period structures (Λ ≈ λ, λ/2 and λ/4) in samples statically irradiated at the same wavelength. More recently, femtosecond-laser pulses at 1030 nm have been used to generate ablative ⊥-LIPSS with a very small period [16] (Λ ≈ λ/9) using a slow beam scanning speed.…”
Section: Introductionmentioning
confidence: 99%
“…A great many research works have been done in this field in past several decades [2][3][4][5][6][7][8][9][10][11][12] . For instances, nanogratings were produced by radial and azimuthal laser polarization modes [13] , pyramid-like spikes in a single crystal superalloy upon irradiation with picosecond laser pulses were investigated [14] .…”
Section: Introductionmentioning
confidence: 99%